The Role of Leadership and Motivation in Mediating the influence of the Work Environment on the Performance of Banking Employees during the Covid-19 pandemic - Pasagi, Yunior; Mulyanti, Rita Yuni; Herningsih, Herningsih (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the role of leadership and motivation in mediating the influence of the work environment on the performance of employees of PT. Bank Mandiri Sorong branch during the covid 19 pandemic. The population in this study were all employees of Bank Madiri Sorong branch with saturated sampling technique. The method of analysis in this research is Structural Equation Modeling (SEM) based on Variance Based or known as Partial Least Square (PLS-SEM) using Smart PLS v3.3.3 software. Findings. The results showed that the work environment did not directly affect the performance of the employees of Bank Mandiri Sorong Branch. Leadership and motivation can mediate the influence of the work environment on the performance of employees of Bank Mandiri Sorong Branch. The results of this study can be information for the manager of the Sorong branch of Bank Mandiri that to improve the performance of their employees during the covid-19 pandemic, they cannot rely on the work environment alone, but must also be supported by respectful leadership and motivation in the form of health insurance.